Climate Concern and Engagement: Large Face-to-Face and Online Polls by the Dutch non-profit Milieudefensie. (26th April 2023) - Bosshard, Anna; Chatrou, Anne; Brick, Cameron
Abstract: Climate change mitigation depends on tracking public opinion across populations. Social scientists can collaborate with environmental organizations that conduct surveys among their audiences. We teamed up with the non-profit Milieudefensie, who surveyed Dutch attitudes towards climate change in 2019–2020. The large dataset had face-to-face ( n = 3, 102) and online interviews ( n = 30, 311) of urbanity, climate concern, policy preferences, interviewer-rated engagement with climate change, and behavior (whether the interviewee provided their email and phone number to the organization). To reveal the representativeness of these kinds of convenience samples, we tested whether attitudes and their associations with behaviors were similar to previous studies. Climate concern, preference for climate policy, and interviewer-rated engagement were high. In the online survey, 47% of respondents signed up for an email newsletter, and 7% provided their phone number. Higher climate concern and preference for climate policy predicted interviewer-rated engagement and behavior (weak to strong associations). Urbanity was not related to concern, policy preferences, or interviewer-rated engagement. Policy preferences did not differ between the face-to-face and online samples. The results provide convergent evidence to conventional online surveys. These Dutch residents appear slightly more engaged with systemic change to mitigate climate change than the general public.